2011
DOI: 10.1590/s2179-975x2011000200006
|View full text |Cite
|
Sign up to set email alerts
|

Controlling factors of benthic macroinvertebrates distribution in a small tropical pond, lateral to the Paranapanema River (São Paulo, Brazil)

Abstract: AIM: The aim of the present study was to examine the benthic fauna in a marginal pond lateral to the Paranapanema River and to identify the main controlling factors of its distribution. Considering the small size of the lacustrine ecosystem, we expected that seasonal variations of the benthic community attributes are more important than spatial variations; METHODS: Two samplings, one in March and another in August, were carried out at nine sites in the pond. Sediment samples were obtained through a Van Veen gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…This is not totally strange as the sediments in tropical lakes and reservoirs have been reported to be mostly acidic (Jackson, ; Singare et al ., ). The acidic nature of the sediment could be attributed to intense degradation of organic matter in the reservoir (Shimabukuro and Henry, ). Increased growth of aquatic weeds and algae in the dry season could be responsible for the higher pH values recorded for the season.…”
Section: Discussionmentioning
confidence: 99%
“…This is not totally strange as the sediments in tropical lakes and reservoirs have been reported to be mostly acidic (Jackson, ; Singare et al ., ). The acidic nature of the sediment could be attributed to intense degradation of organic matter in the reservoir (Shimabukuro and Henry, ). Increased growth of aquatic weeds and algae in the dry season could be responsible for the higher pH values recorded for the season.…”
Section: Discussionmentioning
confidence: 99%
“…The dissolved oxygen and depth are also key factors for the distribution of macroinvertebrates (Santos & Henry, 2001;Shimabukuro & Henry, 2011). The depth at site 3 is smaller than the other sites.…”
Section: Discussionmentioning
confidence: 99%
“…Alkalinity, pH and Dissolved Oxygen were shown as the most important environmental factors, as they were associated to the decomposition of organic matter. Shimabukuro & Henry (2011) found that lower pH and Dissolved Oxygen are derived from ions released during leaf decomposition.…”
Section: Discussionmentioning
confidence: 99%